2022
DOI: 10.3390/f13020324
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Plant Responses to Water Stress and Related Genes: A Review

Abstract: Drought and waterlogging seriously affect the growth of plants and are considered severe constraints on agricultural and forestry productivity; their frequency and degree have increased over time due to global climate change. The morphology, photosynthetic activity, antioxidant enzyme system and hormone levels of plants could change in response to water stress. The mechanisms of these changes are introduced in this review, along with research on key transcription factors and genes. Both drought and waterloggin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 159 publications
0
41
0
1
Order By: Relevance
“…Reducing leaf relative water content, turgor loss, and stomatal closure are the frequent consequences of drought stress in Barley (Hordeum vulgare L.) [51]. During drought, leaf wilting and abscission reduce water loss via transpiration [17,63]. When there is a significant water shortage, cell enlargement in higher plants is hampered by the interruption of xylem water flow.…”
Section: Physiological and Biochemical Responses Under Drought Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Reducing leaf relative water content, turgor loss, and stomatal closure are the frequent consequences of drought stress in Barley (Hordeum vulgare L.) [51]. During drought, leaf wilting and abscission reduce water loss via transpiration [17,63]. When there is a significant water shortage, cell enlargement in higher plants is hampered by the interruption of xylem water flow.…”
Section: Physiological and Biochemical Responses Under Drought Stressmentioning
confidence: 99%
“…Lower RWC reduces leaf water potential, causing stomata to contract. T ration is the primary mechanism governing leaf temperature; increasing stoma sistance minimizes the transpiration rate in rice leaves due to ABA content and in leaf temperature [63]. In a Triticum aestivum L., the leaf's relative water content in throughout development and decreases as dry matter accumulates as the leaf ag Water-stressed wheat and rice plants contained less water content as compared to wheat and rice plants that were grown under controlled conditions [71].…”
Section: Leaf Relative Water Content (Rwc)mentioning
confidence: 99%
“…Adverse environments, such as waterlogged soil, may induce several changes at morphological and physiological levels in plants. To enhance waterlogging tolerance, a vast number of stress response genes are activated and essential functional proteins are synthesized [ 122 , 123 ]. Wei et al, (2021) [ 124 ] observed a considerable down-regulation of photosynthesis-related genes (e.g., PsbQ , PsbO , and petF ) and light-harvesting chlorophyll protein complex genes (e.g., LHCB1 , LHCB3 , LHCB5 , LHCA1 , and LHCA4 ) in two wheat genotypes in response to waterlogging.…”
Section: Plant Responses To Waterloggingmentioning
confidence: 99%
“…Under water excess conditions, the signals originating from the root system are transferred to the soil, causing the stomata to close and, consequently, minimizing the photosynthetic rate and the absorption and assimilation of CO2 (Wu et al, 2022). Moreover, water stress results in a significant accumulation of osmolytes in plants, decreasing the plant osmotic potential to maintain water status and physiological activities required by plants (Mukherjee et al, 2022).…”
Section: Physiological Responses Released By Soil Excess Water and It...mentioning
confidence: 99%